1999
DOI: 10.1159/000020891
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors of Hypoglycemia in Premature Infants

Abstract: Hypoglycemia is a frequent complication of preterm birth and may lead to later CNS damage. The hypoglycemia incidence and the relative risk factors for the affected preterm infants were assessed. We examined 1,500 preterm infants (<37 weeks of gestational age) consecutively admitted between January 1994 and December 1996 at the Department of Pediatrics of Padua University, and screened for hypoglycemia by Dextrostix within the first hour of life. Hypoglycemia was defined as blood glucose levels <40 mg% at Dext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 17 publications
1
9
0
Order By: Relevance
“…This may be related to the relative increase in body surface area, depleted energy stores or peripartum compromise. They are also at increased risk of hypoglycaemia, most probably because of depleted energy stores and perinatal compromise, and require the longest duration of intravenous glucose infusion [6,24,25]. They also are at increased risk for all grades of ROP, confirming other reports where, after adjustment for perinatal risk factors, very low birth weight premature infants who were also SGA had a 2.06-fold risk for Grade 3 to 4 ROP [16,[26][27][28].…”
Section: Discussionsupporting
confidence: 76%
“…This may be related to the relative increase in body surface area, depleted energy stores or peripartum compromise. They are also at increased risk of hypoglycaemia, most probably because of depleted energy stores and perinatal compromise, and require the longest duration of intravenous glucose infusion [6,24,25]. They also are at increased risk for all grades of ROP, confirming other reports where, after adjustment for perinatal risk factors, very low birth weight premature infants who were also SGA had a 2.06-fold risk for Grade 3 to 4 ROP [16,[26][27][28].…”
Section: Discussionsupporting
confidence: 76%
“…This study found at least 1 episode of hypoglycemia in 32% and hyperglycemia in 27% of neonatal patients, consistent with the percentages others found: an incidence of hypo-and hyperglycemias of 35% and 24%, respectively, although slightly different definitions were used in their studies (<2.2 mmol/L and >12 mmol/L, respectively). 9,42 Limitations Potential confounding in ITS studies is limited to factors that are related to the outcome, and that changed at the time of the intervention, such as cointerventions, seasonal changes, changes in measurement of the outcome, and changes of the study population during the time of intervention. 27 As mentioned before, this study's time span was long enough to rule out seasonal changes, and NICU policy concerning plasma glucose concentration measurements, cutoff points for hypoand hyperglycemia, and associated treatment consequences remained unchanged.…”
Section: Discussionmentioning
confidence: 99%
“…Risk factors for glucose imbalance were prematurity (<37 weeks gestational age), small for gestational age (SGA; birth weight <2.5th percentile for gestational age), maternal diabetes, or macrosomy (birth weight >97.7th percentile for gestational age). 9,[23][24][25] Patients with an insulinoma were excluded. Informed consent was waived by the hospital's medical ethics committee.…”
Section: Setting and Study Populationmentioning
confidence: 99%
See 1 more Smart Citation
“…Newborns who have a high-risk of hypoglycemia and need of hypoglycemia screening in the first hour of life [22] are newborns who weigh more than 4 kg or less than 2 kg, large for gestational age (LGA) infants who are above the 90th percentile, small for gestational age (SGA), infants below the 10th percentile [23], and infants with intrauterine growth restriction [24][25][26][27][28][29][30][31]. In addition, high risk newborns are children with gestational age less than 37 weeks, children with sepsis [32] or born to a mother having chorioamnionitis or toxemia.…”
Section: High Risk Neonatesmentioning
confidence: 99%